PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL (HAKI) MEREK TERKENAL UNTUK MENJAGA REPUTASI PERUSAHAAN - Mastur Mastur (LP2M, 2016)
Intelectual Property Rights generally appear from human intelectual capability. The creations includes of technology, science, art and literature working. One of IPRs segment is brand. A famous brand is gained from hard effort which long process and good planning strategy. It becomes urgent because just famous brand that could defend on business global competition, while the unfamous brand gets many constraint from consumer society. Brand imitation of famous brand has been happening in our society so that impacts both economic and non economic for their companies. Although law protection has regulated on UU 15/2001. Famous brand could be measured from many parameters eg : consumer degree of recognition, widely spread of used society and society used duration of the product. Brand violation is generally motivated for taking easy benefit with try, imitate, duplicate famous brand. This behaviour could injure other parts like as society, producer, consumer, beside governments. Dispute completion of brand violation could be solved through civil or criminal process and arbitration solution via alternative institution of dispute settlement Keywords : law protection, brand, company reputation